Structural and optical properties Investigation of ZnxCd1-xS thin films (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
CdZnXS1-X thin films with different composition have been deposited on glass substrate by by the spray pyrolysis method at RT using CdCl2 (0.1M),ZnCl2(0.1M)and H2NCSNH2(0.1M)solution and a substrate temperature of ( 400±20°C). X-ray diffraction studies reveal that the films are polycrystalline in nature with hexagonal structure and preferential orientation along (002) . The grain size of the films is found to increase form  (37.397 to 46.902) nm with increasing Zinc concentration while the strain and the dislocation density of the films are found to decrease from (7.15 to 4.54) 10 4 rad and from (3.82 to 1.93) 10 14 lines.m-2 respectively . The  transmittance  spectrums  of  CdZnxS1-x  thin  films  reveal very pronounced interference effects for photon energies below the fundamental absorption edge by exhibiting interference pattern . The optical energy gap for CdZnxS1-x thin films increases and shifts towards the UV region  as the  Zn concentration in the films increased .